Strange bedfellows: austerity and social justice at the neoliberal University - Muzzatti, Stephen L. (Critical criminology, 2022)
This article examines some aspects of the operation of universities under neoliberalism in Canada and the USA. It begins with a short overview of neoliberalism’s impact on higher education, subsequently turning to a discussion of some of the defining characteristics of the twenty-first century neoliberal university. Particular attention is paid to an ethos of corporate managerialism amongst university administrators and how that is manifested in the intersecting strategies of privatisation, monetisation, resource reallocation and the subtle regulation of faculty. Following an exploration of some claims-making about the instrumentalism of higher education, the article highlights the shifting narratives that emanate from universities’ communications and strategic planning offices. Paying particular attention to contemporary universities’ peculiar brand of progressive neoliberalism, the article concludes with an analysis of the appropriation of social justice in service of undergraduate recruitment.